Automatic Snorkeling Electronic Equipment Enabled by Self‐Breathing Flexible Aqueous Aluminum‐Air Battery. Issue 2 (30th October 2022) - He, Ning; Ling, Wei; Ji, Xixi; Yu, Chengrong; Liu, Shang; Qin, Bao; Zhang, Xuan; Zhou, Yexin; Mo, Funian; Lei, Hao; Zeng, Lin; Lin, Meng; et al.
Abstract: Snorkeling equipments have played a vitally important role in various underwater operations, such as military, rescue activities, underwater research, archeology, and so on. However, existing snorkeling styles, represented by mechanical lifting system, artificial diving, and submarine mode (water storage and drainage), still face numerous challenges in the issues of large energy loss, complex structure, or environmental unfriendliness. Especially for small flexible equipments, an efficient and convenient way of snorkeling is of prime importance to various underwater explorations for a long time. Here, for the first time, an automatic snorkeling electronic equipment driven by a self‐breathing flexible aqueous aluminum‐air battery (Self‐BAAAB) which integrates functions of the snorkeling and the electric energy supply is designed. The self‐BAAAB battery consists of naturally inspired spongy sodium polyacrylate (PANa) hydrogel that acts as a flexible electrolyte and vertical N–O doped graphene fiber (NOGF) as an ORR/OER/HER trifunctional electrocatalyst. Benefited from the trifunctional catalytic properties and the aluminum metal stripping, the Self‐BAAAB consumes oxygen gas in the routine discharge process while the gas in turn is released during the charging process due to electrolysis of water in the super‐absorbing hydrogel, which triggers the sharp density variation of Self‐BAAAB, driving the "automatic snorkeling" feature of electronic equipment underwater. This work provides new insights into the design of the snorkeling electronic equipments and would promote the high efficiency of underwater operations, especially in a complex environment. Abstract : An automatic snorkeling electronic equipment is driven by self‐breathing flexible aqueous aluminum‐air battery (Self‐BAAAB) via developing spongy PANa hydrogel as a flexible electrolyte and vertical N–O doped graphene fiber (NOGF) as ORR/OER/HER trifunctional electrocatalyst, resulting in a convenient and low energy consumption snorkeling of underwater electronic equipment and further promoting the high efficiency of underwater operations, especially at complex environment.